COMMUNICATIVE MOVES IN THE DISCUSSION SECTIONS OF EFL INDONESIAN VOCATIONAL COLLEGE STUDENTS - Titik Rahayu; Muhyiddin Aziz; Moh. Farid Maftuh (ELTR Journal, 2023)
Studies on the move analysis in the various sections of research articles have developed rapidly. However, the studies on the communicative moves in the discussion section particularly written by vocational college students are still limited. In fact, those students categorized as the novice writers inevitably need illustrations of how to write the proper discussion related to their findings. Therefore, this study was aimed at exploring the communicative moves and the move cycle series in the discussion sections of the final project reports written by EFL vocational college students in one of the state polytechnics in Indonesia. The method used is a discourse analysis on 15 discussion sections. The results showed that Move II, Move IV, and Move I were used frequently in all students’ discussion sections. Pertaining to the move cycle series, students fulfilled the rhetorical functions of introduction (1) and evaluation (4+2 or 2+4) but the cycle for showing the conclusion was commonly not used. The results provide references and the real applications pertinent to communication moves in the discussion section by EFL students.